Penerapan Arsitektur Healing Environment dalam Perancangan Pusat Pelayanan Kesehatan Holistik di Kota Makassar - Al-Faaruuq, Aryun Muhammad; Alfiah, Alfiah; Nuryuningsih, Nuryuningsih (TIMPALAJA : Architecture Student Journals, 2025)
Makassar City faces the issue of increasing psychological stress among urban communities and the need for health services that are not only curative but also preventive and rehabilitative. This study aims to design a Holistic Health Service Center with a healing environment approach that integrates physical, psychological, social, and spiritual aspects within a unified site. The methods used include literature review, spatial document review, site observation and analysis (accessibility, orientation, noise, vegetation, and microclimate), user needs mapping, space programming, concept development, and design evaluation against healing environment criteria. The design results in an area design in Tallasa City, Tamalanrea, with two main service masses, front-rear parking separation, a shaded pedestrian network, and clear public, semi-public, and private zoning. Green open spaces, therapeutic gardens, and healing vegetation are key elements, while supporting facilities such as youth & art rooms, gymnasiums, plazas, mosques, and pharmacies are integrated to encourage therapeutic and social activities. The design of the mass, opening orientation, and materials are selected to maximize natural lighting, cross-ventilation, and thermal comfort. Overall, the design creates a functional, understandable, and calming service environment, which is expected to enhance the user's holistic recovery experience and quality of life.